Investigating The Impact Of Reversion Of Single National Curriculum At Primary Level In Azad Jammu Kashmir - Alam Ishtiaq, Tanveer; Sumaera Mahmood; Taqdees, Nayyab (JCTE, 2026)
This qualitative method research aimed to assess the effectiveness of a more recently developed Curriculum, called Single National Curriculum (SNC) by the government of Ex- Prime Minister, Mr. Imran Khan in 2018- 19. The aim of the study to explore the impact of causes of reversion of SNC in AJK at primary level, the research instrument(s) included standard examination tests and a semi-structured interview from teachers. The population for this study included 160 students in four public and four private schools of District Kotli. Teachers think that reintroducing Single National Curriculum will significantly raise the educational standards of education. It is however surfaced that the implementation of Single National Curriculum of any other curriculum, for that matter, require great amount of groundwork and preparing teachers through extensive teacher training programmed.